Soybean response (Glycine max L.) under the use of biostimulants: A literature review - João Henrique Barbosa da Silva; Antônio Veimar da Silva; Carla Michelle da Silva; Philip Moab Duarte Amorim; Ellen Vitória Barbosa do Carmo; Kelson da Silva Carvalho; Arthur Henrique Peixe da Cunha Martins; Karla Cristina de Barros Franca; Bianca Alves Custódio; Erisson Marques da Silva; Francisco Pereira dos Santos Filho; Ozael David Valério da Silva; et al. (Scientific Electronic Archives, 2023)
Soybean (Glycine max L.) is a crop with prominence in Brazil and worldwide. The increase in soybean production and production capacity is associated with scientific and technological advances in the productive sector. One of these advances is the use of biostimulants. In this sense, this work aimed to review current knowledge about the effects of biostimulants on soybeans, highlighting the direct or indirect response of the plant when using such substances. This review was carried out through a research with a qualitative approach, being considered a literature review of the narrative type, using other studies and research at the same theme, in high impact magazines from the last five years or more that were relevant to the study, with subsequent critical reading about the subject. Based on found results, it is clear the use of biostimulants in soybeans is a potential alternative input for increasing the growth and development of the crop, as they are able to provide increments in its productive variables. However, further research is needed in order to provide better information on agronomic interests.